Investigating the Structure and Dynamics of Knowledge Sharing Behaviour and Enterprise Social Networking - Fazil, Urfa; Mehmood, Nasir; Hussain, Kamil (UW Journal of Management Sciences, 2023)
Introduction: Enterprise social networking (ESN) strategies have been widely adopted by businesses as a way to provide a venue for open employee communication. This study looks into how factors influencing knowledge sharing behaviour affect the use of enterprise social networking. It is based on the social capital idea. Knowledge sharing behaviour is influenced by knowledge donating and knowledge collecting. Methodology: A self-administered survey of 380 telecommunications industry workers in the Punjab region of Pakistan was conducted. Smart PLS was used for statistical analysis by applying Structural Equation Modelling (SEM) technique. Findings: The results demonstrate significant positive relationships between the knowledge sharing behavior and enterprise social networks. Employees perform better when engaged themselves in using social enterprise networks for information and knowledge sharing. Both knowledge sharing and knowledge collecting behavior strengthen the use of Enterprise Social Networking. Keywords: Knowledge Sharing Behaviour, Knowledge Collecting, Knowledge Donating, Enterprise Social Network, Social Networking.